Sosialisasi pentingnya layout toko untuk meningkatkan penjualan - Aprilda Yanti aprilda; Muhammad Asyari Syahab (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2023)
Friendly service is the key to being able to maintain a retail business amidst the many similar retailers emerging. Arranging the store layout and visual merchandising of the store is one of the keys to providing friendly service. Providing a unique interior design for your shop or place of business is one of the best ways to increase consumer interest in visiting your shop so that it can increase the number of shop sales. Arranging the shelves and merchandise in the shop is an important prerequisite in a retail outlet because a good layout will provide many benefits for the company in the process of completing the work. Besides that, a good layout will also make it easier to carry out work mechanisms, influence work productivity both positively and negatively and provide excellent service effects to customers.